Web browser incorporating social and community features - Lavista Ferres, Juan M.; Kahan, John B. (US Patent 16043836, 2020)
Systems, methods, and apparatuses are provided for enabling a web browser to incorporate social and community features. In one aspect, the web browser may provide and/or receive feedback from a feedback repository server corresponding to a website being accessed. The web browser may display the received feedback along with web page content received from a server hosting the website. In another aspect, the web browser may initiate a two-way communication channel with a communication server by transmitting and/or receiving one or more messages corresponding to a particular website that is being accessed in the browser. The communication channel may be initiated between other users visiting the same website, or between a visitor to a website and an endpoint associated with an owner of the website. The web browser may display website content received from a web hosting server, along with the messages sent or received from the communication server.